PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN TEKNIK AKROSTIK SISWA SMP KRISTEN EBEN HAEZAR MANADO - Nontje Deisye Wewengkang (Balai Bahasa Sulawesi Utara, 2011)
The aim of this research is to develop poetry writing ability on grade 7 students of Eben Haezar 2 Middle School in Manado. The design of this research is Class Action Research. The indicators such as diction, ﬁgurative language, rhyme, and image. The objects of this research are the 7 C students of Eben Haezar 2 Middle School which are comprised of 28 students. The data of this research are verbal and non-verbal data. The data were obtained by observing, recording, interview, and documentation. The data are analyzed using a qualitative method, such as classiﬁcation, reduction, explanation and analyses, and conclusion. The result of this research shown that was ability increasing on poetry writing with acrostic technique including learning planning, implementing and the lesson learned.